Civil war on the Central Plains: mobilization, militarization, and the end of Nationalist rule in Zhengzhou, 1947-1948 - Baker, M (Johns Hopkins University Press, 2020)
The railroad junction city of Zhengzhou in Henan Province was a key Nationalist strongpoint in the Chinese Civil War, a well-guarded city that would be “defended to the death.” But what did the encroaching conflict mean for the city and its inhabitants? This article breaks new ground by exploring the tense relationship between local authorities and residents during the last months of Nationalist rule. Using eyewitness accounts, newspapers, and sources surviving in the municipal archive, it uncovers struggles over refugees, taxes, corvée labor, and the militarization of the city. In each case, state-society relations in Zhengzhou were damaged by both Nationalist misgovernance and the sheer cost of total war in an exhausted region. By the long, hot summer of 1948, the authorities had little to offer Zhengzhou’s residents and were concerned only with their own institutional survival. The Nationalist government had become what we might call a “state for itself.”